Designing an Auto Retractable, Manual Retractable & Permanent Car Cover to Provide Shelter from Heat & Rain during Moving & Stationary (Parking) - Abdullah, Zulkeflee (2006)
The project aims to design & manufacture a permanent car cover that has aerodynamic shape to be of shelter to car & hence reduce the temperature & give comfort to the car user. Malaysian hot climate leaves a car extremely heated up. Furthermore, the extra light from the sun affects visibility. Heavy rain can also reduce visibility when the raindrops hit the windshield. These may contribute to road accidents. A concurrent design approach will be used in designing and doing prototype for this device. The analysis includes analysis on aerodynamic capacity of the design for permanent cover & moving car. Beside that the research will study & use the appropriate material that can absorb and/or reflect heat & hence not disperse it to the car. A device will be designed & analysed which can reduce the heat imposed by the hot sun. It will cover up the roof of car. It is hope that with this device people can be more comfortable in their vehicle. Beside that several alternatives is given to the user to choose which kind of shelter is best for them, namely auto/manual retractable cover or permanent cover. People will feel more comfortable & less stress while driving hence reduce accident.